Early Rehabilitation in Patients with Proximal Humeral Fracture: A Comparative Analysis of Functional Outcomes Between Surgical and Conservative Treatments. - Menzo, Maria Venra (Journal of Biomedical Practitioners, 2025)
Proximal humeral fracture is a common trauma, with a significant impact on upper limb function. Treatment options vary between conservative and surgical approaches, while rehabilitation management plays a crucial role in recovering movement and reducing disability. The existing literature highlights a lack of studies in this area, this study aims to compare the functional outcomes of patients with proximal humeral fracture treated with surgical and non-surgical strategies, who underwent a rehabilitation program versus patients who did not perform it, with a further distinction based on the timing of rehabilitation intervention. The Constant-Murley scale indicated a functional score of 33.2 ± 1.9 before rehabilitation treatment, in the face of a functional score post-treatment value of 91.7 ± 2.9 (p < 0.001). The therapeutic success was dictated by the precocity of the rehabilitation intervention, regardless of the surgical or conservative therapeutic choice.